Costs associated with implementation of a strict policy for controlling spread of highly resistant microorganisms in France. Issue 1 (29th January 2016) - Birgand, Gabriel; Leroy, Christophe; Nerome, Simone; Luong Nguyen, Liem Binh; Lolom, Isabelle; Armand-Lefevre, Laurence; Ciotti, Céline; Lecorre, Bertrand; Marcade, Géraldine; Fihman, Vincent; Nicolas-Chanoine, Marie-Hélène; Pelat, Camille; et al.
Abstract : Objective: To assess costs associated with implementation of a strict 'search and isolate' strategy for controlling highly drug-resistant organisms (HDRO). Design: Review of data from 2-year prospective surveillance (01/2012 to 12/2013) of HDRO. Setting: Three university hospitals located in northern Paris. Methods: Episodes were defined as single cases or outbreaks of glycopeptide-resistant enterococci (GRE) or carbapenemase-producing Enterobacteriacae (CPE) colonisation. Costs were related to staff reinforcement, costs of screening cultures, contact precautions and interruption of new admissions. Univariate analysis, along with simple and multiple linear regression analyses, was conducted to determine variables associated with cost of HDRO management. Results: Overall, 41 consecutive episodes were included, 28 single cases and 13 outbreaks. The cost (mean±SD) associated with management of a single case identified within and/or 48 h after admission was €4443±11 552 and €11 445±15 743, respectively (p<0.01). In an outbreak, the total cost varied from €14 864 ±17 734 for an episode with one secondary case (€7432±8867 per case) to €136 525 ±151 231 (€12 845±5129 per case) when more than one secondary case occurred. In episodes of single cases, contact precautions and microbiological analyses represented 51% and 30% of overall cost, respectively. In outbreaks, cost related to interruption of new admissions represented 77–94% of total costs, and had the greatest financial impact (R 2 =0.98, p<0.01). Conclusions: In HDRO episodes occurring at three university hospitals, interruption of new admissions constituted the most costly measure in an outbreak situation.